A SECOND CHANCE FOR ENTREPRENEURS IN THE REPUBLIC OF MOLDOVA: CHALLENGES AND SOLUTIONS - NOVAC, Alexandra; ACULAI, Elena; MAIER, Lidia (Economy and Sociology, 2021)
The relevance of offering a second chance is determined not only by the need to mitigate the consequences of business failure and motivate the entrepreneur to continue his entrepreneurial activity, but also by the impact on the country’s economy, as business closure leads to job losses, a worsening of the financial possibilities of the national and local budgets, reduction of competition and other negative trends in the internal market. The importance of these issues has increased significantly in the context of the COVID-19 pandemic, leading to significant deterioration of the Moldovan business environment. The aim of the paper is to identify the barriers and needs of entrepreneurs, who face financial or other difficulties, are in a state of insolvency, have gone through restructuring/bankruptcy proceedings and would like to benefit from a second chance in Moldova. The research methodology is based on the analysis of legislative acts in the field; statistical data analysis; the results of 16 semi-structured interviews with entrepreneurs on elucidating the factors that favor and hinder the entrepreneurial activity, related to obtaining a second chance in business. The interviews were conducted between April and August 2018. The research results showed that both internal factors (insufficient financial resources, knowledge of crisis management, mismanagement, insufficient staff qualification, including the entrepreneurial skills / experience of the owners, the lack of people with certain professions) and external (related to insolvency legislation, limited information on the possibilities that can be used in case of failure) are determining for taking a second chance.